(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the primary function of phraseological units in the sentence, focusing on their semantic, syntactic, stylistic, and communicative roles. Drawing upon classical and modern linguistic theories, including those of V.V. Vinogradov, A.V. Kunin, I.V. Arnold, A.P. Cowie, and Fernando & Flavell, the article provides a comprehensive overview of how phraseological units operate as integral, indivisible components of sentence structure. The study argues that the core function of phraseological units is their ability to act as a single semantic whole while fulfilling a specific syntactic slot, regardless of their internal lexical complexity. Additional functions—expressive, evocative, pragmatic, and cultural—are also analyzed as secondary but pedagogically significant. The paper concludes that phraseological units contribute to sentence meaning not only through lexical stability but also through enriched expressiveness and cultural information.